Implementasi Sistem IoT untuk Pemantauan Kelembaban dan pH Tanah secara Real-Time pada Tanaman Hortikultura - Surapati, Untung; Farizi, Faradj (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This study develops an Internet of Things (IoT) system to support horticultural farming in Berjo Village, Karanganyar District. The system monitors soil parameters such as pH and moisture in real-time, aiding farmers in making informed decisions regarding fertilization and watering. The implementation aims to improve efficiency and crop yields of cultivated flowers, reducing losses caused by improper soil conditions. Additionally, the paper discusses the role of technology in transforming agriculture, demonstrating that IoT adoption offers innovative solutions to address unpredictable rainfall challenges and foster local interest in flower cultivation. Government support is crucial for the sustainability of this innovation, ensuring it benefits smallholder farmers and enhances agricultural productivity through advanced technology integration.